2016
DOI: 10.1111/hepr.12710
|View full text |Cite
|
Sign up to set email alerts
|

Classification of patients with non‐alcoholic fatty liver disease using rapid immunoassay of serum type IV collagen compared with liver histology and other fibrosis markers

Abstract: Type IV collagen may be a useful measure of NASH severity as latex particle-enhanced turbidimetric immunoassay-based rapid type IV collagen assay can be carried out routinely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 40 publications
3
42
0
3
Order By: Relevance
“…7 Such particle-enhanced turbidimetric immunoassays (PETIAs) have been used since the 1920’s, and currently PETIAs for a variety of analytes are commercially available. 810 Turbidimetric assays have the advantages of being label-free, fast (<20 min), and easy to perform on commonplace equipment (i.e., microwell plate readers). 11,12 One disadvantage of common turbidimetric assays is that they require the use of antibodies, which have poor environmental stability, and the routine methods for antibody production are associated with high cost.…”
Section: Introductionmentioning
confidence: 99%
“…7 Such particle-enhanced turbidimetric immunoassays (PETIAs) have been used since the 1920’s, and currently PETIAs for a variety of analytes are commercially available. 810 Turbidimetric assays have the advantages of being label-free, fast (<20 min), and easy to perform on commonplace equipment (i.e., microwell plate readers). 11,12 One disadvantage of common turbidimetric assays is that they require the use of antibodies, which have poor environmental stability, and the routine methods for antibody production are associated with high cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, current histologic staging systems are not continuous quantitative measures of hepatic fibrosis . Previous studies have suggested that noninvasive or minimally invasive biomarkers, including platelet counts, serum levels of the type IV collagen 7s domain (7s collagen) and Wisteria floribunda agglutinin‐positive Mac‐2 binding protein, fibrosis‐4 (FIB‐4) index, and liver stiffness computed by imaging technologies, are surrogate measurements for estimating the degree of liver fibrosis in patients with NAFLD . Emerging evidence attests to a possible role of fibrosis‐targeted therapy against progressive fibrotic diseases, including NAFLD .…”
Section: Introductionmentioning
confidence: 99%
“…The degree of liver fibrosis is associated with long‐term outcomes in NAFLD patients and liver biopsy is recommended as the gold‐standard method for its staging, but this approach has several limitations. There are several non‐invasive biomarkers and scoring systems, involving the use of combinations of clinical laboratory parameters, for the staging of NAFLD . However, these scoring systems also have limitations.…”
Section: Discussionmentioning
confidence: 99%